Chemical stability of hydrogen boride nanosheets in water - Kurt Irvin M. Rojas (Nature Portfolio, 2021)
Nanoscale boron-based materials are promising for electronic devices, and it is important to understand their chemical stability. Here, hydrogen boride nanosheets are stable against hydrolysis in water, which ab initio calculations attribute to the charge state of boron and the boron-boron bond network.